Guided endodontics: accuracy of a novel method for guided access cavity preparation and root canal location. (3rd October 2015) - Zehnder, M. S.; Connert, T.; Weiger, R.; Krastl, G.; Kühl, S.
Abstract: Aim: To present a novel method utilizing 3D printed templates to gain guided access to root canals and to evaluate its accuracy in vitro . Methodology: Sixty extracted human teeth were placed into six maxillary jaw models. Preoperative CBCT scans were matched with intra‐oral scans using the coDiagnostix ™ software. Access cavities, sleeves and templates for guidance were virtually planned. Templates were produced by a 3D printer. After access cavity preparation by two operators, a postoperative CBCT scan was superimposed on the virtual planning. Accuracy was measured by calculating the deviation of planned and prepared cavities in three dimensions and angle. Ninety‐five per cent confidence intervals were calculated for both operators. Results: All root canals were accessible after cavity preparation with 'Guided Endodontics'. Deviations of planned and prepared access cavities were low with means ranging from 0.16 to 0.21 mm for different aspects at the base of the bur and 0.17–0.47 mm at the tip of the bur. Mean of angle deviation was 1.81°. Overlapping 95% confidence intervals revealed no significant difference between operators. Conclusion: ' Guided Endodontics' allowed an accurate access cavity preparation up to the apical third of the root utilizing printed templates for guidance. All root canals were accessible after preparation.